APLIKASI TOTAL QUALITY MANGEMENT (TQM) PENDIDIKAN TINGGI DALAM RANGKA PELAYANAN PELANGGAN MAHASISWA ASING DI INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA (IIUM) - Ahmad Hamid (Universitas Negeri Jakarta, 2010)
This study aims to describe the role of Total Quality Management in order to increase foreign student customers.The method used is qualitative descriptive method. The selection of this method is to obtain an overall picture of the problem being studied. As for the unit of analysis or research subject as a source of data are the leaders, lecturers, staff, technical supervisors, and the students of International University of Malaysia (IIUM).The data was collected by using questionnaires. Interview method is used to support the research, and the obtained-data was analyzed through triangulation. In general, the results of this study show that continuously improvement and involve all elements of the organization starting from the rector of IIUM to personnel at the technical level in order to improve customer service quality of foreign students. This worked well and coordinated according to the system that has been applied and has been in accordance with international standards. Based on data analysis, it is known that in general, Total Quality Management (TQM) that is applied by the rector of the International Islamic University (IIUM) has reached an optimal point, whether it in terms of Customer Satisfaction, Continuous Improvement, Speaking with Fact, and Respect for People. Thus, it can be concluded that TQM applications in order to improve Customer Service Foreign Students at the International Islamic University Malaysia (IIUM) was a great influence in improving customer service quality of foreign students in accordance with the vision, mission and objectives of the International Islamic University Malaysia (IIUM).